Reorganization policy formulation a study of executive-legislation relations - Apolonio, Honorata F. (Philippine Journal of Public Administration, 1992)
This paper shows the relevance of same basic constructs of public administration in analyzing a case study on the formulation of a public policy--that of reorganizing the bureaucracy. The case study illustrates that to intervene in public policy formulation, the following points must be considered: (1) the major stakeholders must be properly identified and prioritized; (2) the contending interests must be resolved; (3) all relevant constraints must be considered; and (4) there is no clear separation between politics and administration. These points are identified in the dynamic interaction between the Executive and Legislative Branch. The case study also shows that the formulation of public policy serves as an arena of struggle among various power blocs but values and ethics nonetheless affect decisionmaking.